ASSESSMENT OF THE VULNERABILITY DEGREE OF DIFFERENT LITHOLOGICAL FORMATIONS IN THE CATCHMENT AREA OF AGIA EIRINI GORGE, WESTERN CRETE - Bizoura, A.; Lykoudi, E.; Spyridonos, E.; Manoutsoglou, E. (Bulletin of the Geological Society of Greece, 2010)
This paper presents a methodology for assessing the degree of vulnerability of different lithology formations constituting the drainage basin of the gorge of Agia Eirini. The methodology is based on the processing of spatial aspects parameters of lithology, hydrography, geomorphology and the vegetation cover, which are related with the weathering impact on formations either directly or indirectly. Initially a series of primary spatial data on geology, topography, the river network and the land use in the region, were used to produce thematic maps. These maps include the geological map, the digital terrain model (DTM), the map of the land use, and hydrographic maps of density and frequency. By processing the data according to their role in enhancing the vulnerability of formations, the data were determined and the following thematic maps: “Map of geological formations susceptible to weathering”, “Map of hydrographic texture”, “Map of morphological inclinations” and “land use map protecting against the loss of disintegrated material were produced. By appropriate combination of these secondary data, areas of vulnerability of formations were recorded which are shown on a final thematic map. This information is particularly valuable in the management planning and gives the opportunity to evaluate and predict the impact of various proposed projects or future scenarios. They can also be used to identify positions to take necessary measures to protect areas at high risk of loss of material.